2010
DOI: 10.1063/1.3467034
|View full text |Cite
|
Sign up to set email alerts
|

Plasma heat pump and heat engine

Abstract: A model system where cold charged particles are locally confined in a volume V P within a warm plasma of volume V ͑V P Ӷ V͒ is studied. Charged particles mutually repel via a shielded repulsion which is like an effective pressure, i.e., electrostatic pressure P E . The law of thermodynamics involving P E and an equation of state for P E are obtained. It is shown that the expansion/ compression of electrostatic fields associated with charged particles is a new mechanism that converts mechanical work into plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…ψ = ψ + ψ c . Now, in the ideal limit, ψ c → 0, the last term is not required, while the second term is zero because ρ ψ d 3 r = ψ ρ d 3 r = 0, therefore [19,20]. The entropy of ideal dust particles is given by…”
Section: Dust Heating Due To Thermal Electric Field Fluctuationsmentioning
confidence: 95%
See 2 more Smart Citations
“…ψ = ψ + ψ c . Now, in the ideal limit, ψ c → 0, the last term is not required, while the second term is zero because ρ ψ d 3 r = ψ ρ d 3 r = 0, therefore [19,20]. The entropy of ideal dust particles is given by…”
Section: Dust Heating Due To Thermal Electric Field Fluctuationsmentioning
confidence: 95%
“…The cloud and the plasma are considered to be stable (without DA waves or any other type of non-thermal fluctuations). This system is similar to the one considered earlier [19,20] except that now dust particles are also assumed to have finite temperature.…”
Section: Dust Heating Due To Thermal Electric Field Fluctuationsmentioning
confidence: 96%
See 1 more Smart Citation
“…This may be achieved by using the discharge between the electrodes to neutralize the space charge with ions; similar attempts were done to use plasma in the heat pump. [ 51 ] Besides, an additional control over the discharge and current between the electrodes may be achieved by the use of magnetic fi eld which can effi ciently sustain the discharge at relatively low applied voltages. [ 52 ] Among others, the low-current radio-frequency [ 53 ] and dielectric barrier discharges [ 54 ] can be used to create stable low-density plasma in interelectrode gap.…”
Section: Sophisticated Design To Enhance the Effi Ciencymentioning
confidence: 99%
“…Specifically, waves might be amplified through compression 4 and then damp resonantly on a particular species in a switchlike manner at a predetermined moment. 5 It was also suggested that concentrating energy in a compressing plasma in the form of waves can increase the plasma effective compressibility, 6 and recent work 7 has even described the basic thermodynamic cycles whereby the interplay between plasma wave energy and thermal energy could be utilized to construct a plasma heat pump and heat engine. Yet, these studies were focused primarily on linear waves, whereas practical applications may require higher wave amplitudes.…”
Section: Introductionmentioning
confidence: 99%